Efektivitas Dukungan PMO Menggunakan Buku Saku Terhadap Pengetahuan tentang Keberhasilan Pengobatan Pasien Kusta - Wa Ode Suriani; Bahrah Bahrah; Nunuk Pratiwi (Malahayati Nursing Journal, 2025)
ABSTRACT Leprosy is a chronic infectious disease caused by Mycobacterium Leprae with a type of granulomatosa disease of the peripheral nerves mucosa of the upper respiratory tract that can affect any age range. One of the internal factors that plays a role in the success of Morbus Hansen therapy is the level of patient knowledge, Increasing knowledge can be done through auxiliary media, one of which is a pocket book. The purpose of this study is to evaluate the effectiveness of PMO support using a pocket book on knowledge about the success of treatment of leprosy patients at the Pasir Putih Health Center, Manokwari Regency. This study analyzed the knowledge of respondents after being given an intervention to provide a pocket book. one group pre test and post test design. The sample in this study was leprosy patients who were treated at the Pasir Putih Health Center as many as 30 respondents with a sampling technique using purposive sampling. This study analyzed the knowledge of respondents before and after being given a pocket book intervention for 14 days. The research instrument used was a questionnaire of 10 questions. The data taken are primary data and data analysis using non-parametric tests. The results of the study showed that in the intervention group, the average knowledge score of respondents before being given the treatment of giving the pocket book was 77, and after the intervention there was an increase in the knowledge score to 82 with a p-value of 0.05, which means that there was a difference in the respondents' knowledge score about the success of the treatment of leprosy patients using the pocket book before and after the treatment. The conclusion is that the pocket book is effective in increasing respondents' knowledge about the success of treatment of leprosy patients. The provision of pocket books can be used as an educational medium in helping the success of treatment of leprosy patients at the Health Center. Keywords: Leprosy Patient, Knowledge, Pocket Book.  ABSTRAK Kusta merupakan penyakit menular kronis yang disebabkan oleh Mycobacterium Leprae dengan tipe penyakit granulomatosa pada saraf tepi mukosa dari saluran nafas atas yang bisa menyerang pada segala rentang usia. Salah satu faktor internal yang berperan dalam keberhasilan terapi Morbus Hansen adalah tingkat pengetahuan pasien,Peningkatan pengetahuan dapat dilakukan melalui media bantu salah satunya yaitu buku saku. Tujuan dari penelitian ini adalah untuk mengevaluasi efektivitas dukungan PMO menggunakan buku saku terhadap pengetahuan tentang keberhasilan pengobatan pasien kusta Di Puskesmas Pasir Putih Kabupaten Manokwari. Penelitian ini melakukan analisis pengetahuan responden setelah diberikan intervensi pemberian buku saku. one group pre test and post test design. Sampel dalam penelitian ini adalah pasien kusta yang melakukan pengobatan di Puskesmas Pasir Putih sebanyak 30 responden dengan teknik pengambilan sampel menggunakan purposive sampling. Penelitian ini melakukan analisis pengetahuan responden sebelum dan setelah diberikan intervensi buku saku selama 14 hari. Instrumen penelitian yang digunakan adalah kuisioner berjumlah 10 pertanyaan. Data yang diambil merupakan data primer dan analisa data menggunakan uji non parametrik test. Hasil penelitian menunjukan bahwa bahwa pada kelompok intervensi rerata skor pengetahuan respoden  sebelum diberikan perlakuan pemberian buku saku skor pengetahuan responden dengan rerata 77 dan setelah diberikan intervensi terjadi peningkatan skor pengetahuanmenjadi 82 dengan nilai p-value yaitu 0,05 yang berarti bahwa terdapat perbedaan skor pengetahuan responden tentang keberhasilan pengobatan pasien kusta menggunakan buku saku sebelum dan sesudah perlakuan. Kesimpulan yaitu buku saku efektif meningkatkan pengeahuan responden tentang keberhasilan pengobatan pasien kusta. Pemberian buku saku dapat dijadikan sebagai media edukasi dalam membantu keberhasilan pengobatan pasien kusta di Puskesmas Pasir Putih. Kata Kunci: Pasien Kusta, Pengetahuan, Buku Saku.